Instant Sensitive Measurement of Hg Concentration Using Lab‐on‐a‐Phone Colorimetry. Issue 14 (6th May 2019) - Sajed, Samira; Vafaei, Khosro; Arefi, Fatemeh; Fathollahzadeh, Maryam; Kolahdouz, Mohammadreza; Sadeghi, Mohammad A.; Neshat, Mohammad
Abstract : Mercury is one of the most toxic heavy metals in the environment that can seriously damage the human health. Therefore, the identification of mercury in water sources such as rivers, lakes, and bays is very crucial. Many traditional methods are used for the detection of mercury (II) ions (Hg 2+ ), but they suffer from dependence on expensive and complicated instruments and need time consuming operating process. Herein, a fast, low cost, and accurate lab‐on‐a‐phone device has been introduced for on‐site monitoring of Hg 2+ in ppb level. It detects Hg 2+ based on localized surface plasmon resonance property of gold nanoparticles. The apparatus consists of lightweight opto‐mechanical attachment, wirelessly connected to a smart phone. This method presents a sensitive detection of Hg 2+ in water with a detection limit of 3 nM (≈0.8 ppb). Detection limit of the proposed sensor is well below the maximum allowed containment level of Hg 2+ for drinking water (6 ppb) by the World Health Organization. Abstract : A colorimetric sensor based on aptamer‐gold nanoparticles on a lab‐on‐phone system is introduced. The sensor is capable of detecting mercury in water samples down to 0.8 ppb range. The process is extracting the RGB values for any image taken from a water sample by a smart phone camera and using that to detect the concentration of mercury.